1996
DOI: 10.1095/biolreprod55.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Porcine SRY Gene Locus and Genital Ridge Expression1

Abstract: Porcine SRY gene locus was cloned through use of a strategy of anchored polymerase chain reaction (PCR) amplification from a male pig genomic DNA size-selected library constructed in a plasmid vector as well as 3' reverse transcription (RT)-PCR amplification of porcine genital ridge SRY transcripts. In total, 1664 bp of genomic DNA and 106 bp of 3' cDNA are presented. The open reading frame of porcine SRY consists of 624 bp representing 208 amino acids (aa) with a centrally located HMG box domain of 79 aa, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…Since in Sox9 -/-mouse gonads Sry persists, results indicate that Sox9 may be involved in repression or down-regulation of Sry [Chaboissier et al, 2004;Barrionuevo et al, 2006]. However, in human [Hanley et al, 2000], sheep [Payen et al, 1996], pig [Daneau et al, 1996;Parma et al, 1999], dog [Meyers-Wallen, 2003] and, as shown in the current study, also in rabbit, SRY expression is not extinguished abruptly as in mouse [Koopman et al, 1990;Hacker et al, 1995]. Species variations probably exist with respect to factors involved in retroactivation of the SRY promoter and in critical sites for gene function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in Sox9 -/-mouse gonads Sry persists, results indicate that Sox9 may be involved in repression or down-regulation of Sry [Chaboissier et al, 2004;Barrionuevo et al, 2006]. However, in human [Hanley et al, 2000], sheep [Payen et al, 1996], pig [Daneau et al, 1996;Parma et al, 1999], dog [Meyers-Wallen, 2003] and, as shown in the current study, also in rabbit, SRY expression is not extinguished abruptly as in mouse [Koopman et al, 1990;Hacker et al, 1995]. Species variations probably exist with respect to factors involved in retroactivation of the SRY promoter and in critical sites for gene function.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in humans [Salas-Cortes et al, 1999;Hanley et al, 2000], sheep [Payen et al, 1996], swine [Daneau et al, 1996;Parma et al, 1999] and dog [Meyers-Wallen, 2003] SRY remains expressed over several weeks after overt morphological differentiation of the testis.…”
mentioning
confidence: 99%
“…6) Sry expression in mouse genital ridges is transient, starting at 10.5 dpc and ending at 12.5 dpc when Amh begins to be expressed (Hacker et al, 1995). On the contrary, in other mammals, SRY expression persists for many days after seminiferous cord formation (Daneau et al, 1996;Payen et al, 1996;Parma et al, 1999;Hanley et al, 2000). Another difference between mouse and other mammals with respect to SRY is the presence of a glutamine-rich domain only in the mouse protein (Whitfield et al, 1993).…”
Section: Expression Profiles Of Foxl2 and Pisrt1 In The Mousementioning
confidence: 99%
“…In the mammalian male embryo, the first molecular signal of sex determination is the expression of the Y-linked gene SRY within a sub-population of somatic cells of the indifferent male genital ridge (Koopman et al, 1990;Daneau et al, 1996;Hanley et al, 2000). In the mouse, the transient expression of Sry between embryonic day 10 (e10.0) and e12.5 drives the initial differentiation of pre-Sertoli cells that would otherwise follow a ''female default pathway'' becoming granulosa cells (Albrecht and Eicher, 2001;Sekido et al, 2004).…”
Section: Introductionmentioning
confidence: 99%